Analisis Faktor-faktor yang Berhubungan dengan Kejadian Bayi Berat Lahir Rendah di Ruang Mawar BLUD RSUD dr.Doris Sylvanus Palangka Raya - Erina Eka Hatini (Jurnal Forum Kesehatan, 2018)
According to the World Health Organization (WHO), around 20 million babies with low birth weight and 19 million are born worldwide born in several developing countries with an incidence rate between 11-13%. Based on the results of the Intercensal Population Survey (SUPAS), 2015 showed that IMR in Indonesia decreased by 22.23 per 1000 live births from 2012, namely 32 deaths per 1,000 live births. This study aims to anaysys of factors related to the incidence of low birth weight (LBW) babies in the Mawar Room of BLUD RSUD dr.Doris Sylvanus Palangka Raya. This descriptive study was using primary data obtained through interviews. Samples in this study amounted to 33 people, based on the largest LBW is a birth weight between 1500 to 2500 grams (84.8%), mothers age are < 20 or > 35 years(66.7%), working mother (84.8%), based and secondary education ( 87,9%), premature pregnancy (66.7%), primiparous and grandemutiparous parity (57.6%), history of ANC visits not according to standard (87.9%), those not exposed to cigarette smoke during pregnancy (84.8%), there was a history of illness or complications in pregnancy (84.9%), with the type of illness suffered by the mother during pregnancy(84,8%), the most were Preeclampsia and Early Rupture (21.4%) But the result of bivariate statistical analysis is no factors showed significant p value, because the number of sampels was too small. The highest LBW was birth weight between 1500-2500 gram, maternal age are 20-35 years old, working mother, based and, secondary education, premature pregnancy, primiparous and grandelultiparous parity, history of ANC visits not according to standard, those not exposed to cigarette smoke during pregnancy, a history of illness or complications in pregnancy, with the most types of diseases suffered by mothers during pregnancy are Preeclampsia and Early Rupture Membrane. The result of this study no factors showed significant p value